Clinical characteristics and factors associated with the severity of hand, foot, and mouth disease in Mekong Delta, Vietnam - Thi Van Vo; Phuong Minh Nguyen; Hau Trung Tran; Tran Huynh Ngoc Thai; Quang Chi Ngo; Dien Tri Lu; Hung Huynh Vinh Ly; Trinh Nguyen Ngoc Luu (International Journal of Adolescence and Youth)
Background Hand, foot, and mouth disease (HFMD) is a contagious viral illness caused by enteroviruses, potentially leading to severe complications like encephalitis, myocarditis, and acute pulmonary edema.Objective This study examines clinical features and risk factors for HFMD severity.Materials and Methods A cross-sectional analysis of 200 children under 16 years.Results Oral ulcers (78.0%) and erythematous rashes (64.0%) as the most common symptoms. High fever (≥39°C), fever lasting over two days, and myoclonus were frequently observed. Notably, 25.5% of cases progressed to severe HFMD during hospitalization. Multivariate logistic regression identified ataxia (OR = 31.645, p = 0.024), tachycardia (OR = 41.882, p < 0.001), and exposure to crowded public places (OR = 3.587, p = 0.046) as key risk factors.Conclusion These findings underscore the need for early detection and targeted interventions to reduce complications and improve outcomes. Strengthened surveillance and preventive measures are crucial in managing HFMD in children effectively.